2019
DOI: 10.1371/journal.pone.0222118
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical alterations in left ventricular structure and function according to obesity and metabolic health status

Abstract: BackgroundObesity and metabolic syndrome (MetS) are associated with high risk of cardiac dysfunction and heart failure. We assessed the effect of obesity and metabolic health status on left ventricular (LV) structure and function in subjects without overt heart disease.MethodsIn 789 subjects (58.8±13.0 years, 50.7% males) without overt heart disease, LV morphology and function were compared among 6 groups stratified by body mass index (BMI) (normal weight, overweight and obese) and metabolic health status (mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
1
32
0
2
Order By: Relevance
“…Previous studies showed that lean subjects with insulin resistance have an unfavorable inflammatory profile with elevated tumor necrosis factor-α and interleukin-6, while obese subjects exhibited a comparable inflammatory status regardless of insulin resistance [ 41 , 42 ]. In addition, obese individuals often have hypertension and sleep disorders such as sleep apnea, which can deteriorate LV function and may attenuate the association between insulin resistance and subclinical LV dysfunction [ 31 , 43 , 44 ]. Indeed, abnormal HOMA-IR was reported to be an independent predictor of cardiovascular mortality in normal weight individuals but not in overweight/obese individuals in the community-based cohort study [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that lean subjects with insulin resistance have an unfavorable inflammatory profile with elevated tumor necrosis factor-α and interleukin-6, while obese subjects exhibited a comparable inflammatory status regardless of insulin resistance [ 41 , 42 ]. In addition, obese individuals often have hypertension and sleep disorders such as sleep apnea, which can deteriorate LV function and may attenuate the association between insulin resistance and subclinical LV dysfunction [ 31 , 43 , 44 ]. Indeed, abnormal HOMA-IR was reported to be an independent predictor of cardiovascular mortality in normal weight individuals but not in overweight/obese individuals in the community-based cohort study [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low GLS values demonstrated higher BMI (30.4 ± 5.7 vs. 26.4 ± 5.0, p = 0.005). Lee et al reported that obesity led to a decrease of GLS by 0.152% per 1 kg/m 2 change in BMI [42].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between EATV and LV strains remains to be elucidated. Previous studies indicated that an increase in the BMI ( 12 14 ) was correlated with reduced GLS. Further, the current study clarified that EATV was a determinant of LV GLS independent of BMI in patients with preserved LVEF.…”
Section: Discussionmentioning
confidence: 96%
“…Poor GLS could be a marker of early cardiac dysfunction in obese individuals. There were reports that body mass index (BMI) ( 12 14 ) or visceral fat area (VFA) ( 15 ) was negatively associated with GLS. It has been suggested that the accumulation of epicardial adipose tissue (EAT) underlies cardiac dysfunction in obesity ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%